Gunung Mulu National Park : A heaven for Aroiders. Part 1. - Wong, Sin Yeng; Boyce, Peter C. (The International Aroid Society, Inc., 2007)
It is a breathtaking experience when you first visit Gunung Mulu National Park in Miri, NE Sarawak. Mulu is truly a wonder of nature and Mulu’s status as a World Heritage Site underlines its outstanding conservation value. But an equally astounding experience is seeing for yourself how rich Gunung Mulu National Park is with aroids. Over a sevenday field trip we made to the lowland areas of the park in August 2006, we encountered ca 80 species of aroids in 18 genera and these just from the most readily accessible day-trip trails.